Diseño de una ruta turística en la parroquia San Juan de Pastocalle, cantón Latacunga, provincia de Cotopaxi - Toaquiza Toaquiza, Lidia Paola (2016)
The present research work called "DESIGN OF A TOURISTIC ROUTE IN THE SAN JUAN DE PASTOCALLE PARISH, LATACUNGA CANTON, COTOPAXI PROVINCE" it was developed based on three strategically established objectives, the first is a diagnosis which helped to get the baseline information on the geographic, social, economic, environmental, tourist and cultural aspect through interviews to the members of the GADPR and the population to know the current status of the sector , the second objective was the study of the market in order to define the tastes and preferences of the tourists and identify the services offered by people there, after that we elaborated the inventory of touristic attractions by applying the methodology of the Ministry where we evaluate and rank every one of them, and in the last one it is designed the touristic routes through the development of methods, techniques and tools for the organization of the visits in the parish and in this way it proposed give to know the natural and cultural resources that has it.